2022
DOI: 10.1111/tesg.12511
|View full text |Cite
|
Sign up to set email alerts
|

More Than Infrastructure Providers – Digital Platforms' Role and Power in Retail Digitalisation in Germany

Abstract: Digital platforms, such as Amazon, represent the major beneficiaries of the Covid-19 crisis. This study examines the role of digital platforms and their engagement in digitalisation initiatives targeting (small) brick-and-mortar retailers in Germany, thereby contributing to a better understanding of how digital platforms augment, substitute or reorganise physical retail spaces. This study applies a mixed-method approach based on qualitative interviews, participant observation as well as media analysis. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 80 publications
(156 reference statements)
0
4
0
1
Order By: Relevance
“…Education shapes the future of any country by empowering its youth and future workforce (Kremer, 1993;Deem et al, 2008;Hardaker, 2022). Online education has been adopted in several countries around the globe in the wake of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Education shapes the future of any country by empowering its youth and future workforce (Kremer, 1993;Deem et al, 2008;Hardaker, 2022). Online education has been adopted in several countries around the globe in the wake of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Stationäre Händler*innen scheinen mehr und mehr in den Fokus etablierter Plattformen zu treten (Hardaker 2022 b). Dies trifft auch auf die 1995 in Kalifornien gegründete Handelsplattform eBay zu.…”
Section: (Lokale) Onlineplattformen Für Einzelhandel Und Innenstadtunclassified
“…Greenstein (2021), while examining the proliferation of digital infrastructures, observed that transformation of digital systems into digital infrastructures does not make universal and economic contribution to society. Hardaker (2022), while examining infrastructuring of digital platforms in replacing brick and mortar retail chains in Germany, observed that such infrastructuring undermines digitalization by shifting power to platforms itself, thereby defeating the very purpose of infrastructuring. Milskaya and Seeleva (2019) analyzed digital economy in Russia and observed that digital infrastructure, on its own, cannot significantly influence the path of digital economy.…”
Section: Research Literature With Contrarian View On Digital Infrastr...mentioning
confidence: 99%